1978
DOI: 10.1071/mf9780275
|View full text |Cite
|
Sign up to set email alerts
|

A Biological Investigation of an Organically Polluted Urban Stream in Victoria

Abstract: The macrofauna of Dandenong Creek, an organically polluted urban stream in Victoria, was studied. It was difficult to separate effects due to pollution from those due to other forms of interference. No true indicator species were found, but seven groups of common animals could be arranged in order of increasing pollution tolerance. Some of the difficulties of using biological systems for stream monitoring are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
9
21
0
1
Order By: Relevance
“…Urban streams had lower family richness, lower SIGNAL scores and lower EPT scores (fewer pollution sensitive families), and the assemblages were differently structured compared with streams that flowed through naturally vegetated catchments. This pattern of degradation in urban aquatic macroinvertebrate assemblages is consistent with other Australian urban waterway studies (e.g., Arthington et al 1982;Campbell 1978;Chessman and Williams 1999;Walsh 2006) and internationally (Roy et al 2003;Gresens et al 2007). As previously reported for urban streams ), analysis of Table 3 The average frequency of the collection of the ten most influential families collected on each sampling occasion (1998)(1999)(2000) from urban and non-urban-impacted sties (sampled at riffle, pool and edge habitats) in the Ku-ring-gai Local Government Area and surrounds (northern Sydney area, south eastern Australia) as identified in SIMPER analysis The level of contribution of each family (in declining order) is given for the difference between the macroinvertebrate assemblages at non-urban and urban-impacted sites Aquat Ecol (2010) 44:685-700 695 catchment and water quality factors revealed that catchment bushland coverage and total catchment imperviousness were highly correlated with invertebrate community structure.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Urban streams had lower family richness, lower SIGNAL scores and lower EPT scores (fewer pollution sensitive families), and the assemblages were differently structured compared with streams that flowed through naturally vegetated catchments. This pattern of degradation in urban aquatic macroinvertebrate assemblages is consistent with other Australian urban waterway studies (e.g., Arthington et al 1982;Campbell 1978;Chessman and Williams 1999;Walsh 2006) and internationally (Roy et al 2003;Gresens et al 2007). As previously reported for urban streams ), analysis of Table 3 The average frequency of the collection of the ten most influential families collected on each sampling occasion (1998)(1999)(2000) from urban and non-urban-impacted sties (sampled at riffle, pool and edge habitats) in the Ku-ring-gai Local Government Area and surrounds (northern Sydney area, south eastern Australia) as identified in SIMPER analysis The level of contribution of each family (in declining order) is given for the difference between the macroinvertebrate assemblages at non-urban and urban-impacted sites Aquat Ecol (2010) 44:685-700 695 catchment and water quality factors revealed that catchment bushland coverage and total catchment imperviousness were highly correlated with invertebrate community structure.…”
Section: Discussionsupporting
confidence: 80%
“…Taxa within the Leptophlebiidae are known for their sensitivity to poor water quality that results from organic and heavy metal pollution (e.g., Chessman 1995; Wright and Burgin 2009). This trend has been reported in several urban stream studies (e.g., Campbell 1978;Arthington et al 1982;Pedersen and Perkins 1986), and it is recognised that their presence or absence strongly parallels the community structural differences between urban and natural waterways.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, among sites of comparable imperviousness, hinterland communities were less degraded than those of the MMA, which were characterized by high abundances of a few hardy taxa, typical of degraded urban stream communities worldwide (e.g. Campbell, 1978; Jones & Clark, 1987; Lenat & Crawford, 1994; Matagi, 1996). Therefore, we hypothesize that the intensively piped drainage infrastructure of the MMA is a more degrading influence than the largely unpiped drainage systems of the hinterland.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of urban impacts on stream macroinvertebrate communities have often confounded sewage and stormwater impacts because of septic tank or combined sewer overflows (e.g. Campbell, 1978; Polls et al ., 1980; Seager & Abrahams, 1990; Willemsen et al ., 1990). Small‐scale studies of the impacts of urban land use, where sewage was not discharged to receiving streams, have consistently shown degradation of community composition (e.g.…”
Section: Introductionmentioning
confidence: 99%